Comparisons of three anterior cervical surgeries in treating cervical spondylotic myelopathy - Zhu, RuoFu (BioMed Central, 2014)
BACKGROUND: Anterior cervical discectomy and fusion (ACDF) was one of the preferred treatments for degenerative cervical spondylosis. However, the motion of adjacent segment was significantly increased after operation. So cervical disc arthroplasty have been suggested to keep the motion of adjacent segment. A new implant named dynamic cervical implant (DCI) has been developed to keep the motion of adjacent segment. METHODS: We retrospectively reviewed 91 patients treated for single level cervical spondylotic myelopathy with anterior cervical discectomy and fusion (ACDF), dynamic cervical implant (DCI) and cervical total disc replacement (CTDR) between sep 2009 and Mar 2011 in our hospital. They were divided into three groups by surgical methods: ACDF group (group A, 34 cases), DCI group (group B, 25 cases), CTDR group (group C, 32 cases). Operation time, intraoperative blood loss, preoperative and postoperative JOA score and JOA recovery rate were compared among the three groups. Pre-and postoperative hyperextension and hyperflexion radiograms were observed to measure range of motion (ROM) of C(2–7), operative and adjacent levels. RESULTS: There was no statistical difference in operative time, intraoperative blood loss, and JOA recovery rate (P > 0.05) among three groups. But the differences of their postoperative JOA scores and preoperative JOA scores were of statistical significance (P < 0.05). Compared the pre-and postoperative ROM of C(2–7), operative, upper and lower levels of each group respectively, the difference between preoperative ROM and postoperative ROM of group A were of statistically significant (P < 0.05), while was no statistically significant of group C (P > 0.05). There was no statistically significant difference between preoperative ROM and postoperative ROM of upper and lower levels in group B (P > 0.05), but had statistically significance of C(2–7) and operative levels (P < 0.05). CONCLUSIONS: Three operations are effective therapies for single level cervical spondylotic myelopathy. But each group has respective advantages and disadvantages.